Nanomelatonin triggers superior anticancer functionality in a human malignant glioblastoma cell line. (18th August 2017) - Kumar Yadav, Sanjeev; Kumar Srivastava, Anup; Dev, Atul; Kaundal, Babita; Roy Choudhury, Subhasree; Karmakar, Surajit
Abstract: Melatonin (MEL) has promising medicinal value as an anticancer agent in a variety of malignancies, but there are difficulties in achieving a therapeutic dose due to its short half-life, low bioavailability, poor solubility and extensive first-pass metabolism. In this study chitosan/tripolyphosphate (TPP) nanoparticles were prepared by an ionic gelation method to overcome the therapeutic challenges of melatonin and to improve its anticancer efficacy. Characterization of the melatonin-loaded chitosan (MEL-CS) nanoformulation was performed using transmission and scanning electron microscopies, dynamic light scattering, Fourier transform infrared spectroscopy, Raman spectroscopy and x-ray diffraction. In vitro release, cellular uptake and efficacy studies were tested for their enhanced anticancer potential in human U87MG glioblastoma cells. Confocal studies revealed higher cellular uptake of MEL-CS nanoparticles and enhanced anticancer efficacy in human malignant glioblastoma cancer cells than in healthy non-malignant human HEK293T cells in mono- and co-culture models. Our study has shown for the first time that MEL-CS nanocomposites are therapeutically more effective as compared to free MEL at inducing functional anticancer efficacy in the human brain tumour U87MG cell line.